2020
DOI: 10.1007/s13311-020-00884-9
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Dexamethasone Reduces Mortality and Brain Damage in a Mouse Experimental Ischemic Stroke Model

Abstract: Neuroinflammation triggered by the expression of damaged-associated molecular patterns released from dying cells plays a critical role in the pathogenesis of ischemic stroke. However, the benefits from the control of neuroinflammation in the clinical outcome have not been established. In this study, the effectiveness of intranasal, a highly efficient route to reach the central nervous system, and intraperitoneal dexamethasone administration in the treatment of neuroinflammation was evaluated in a 60min middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Similar results have been observed in a 60-min middle cerebral artery occlusion stroke model. IN DEX reduced strikingly the ischemic brain tissue damage, reduced blood-brain barrier permeability, decreased mortality and improved the Neurological deficit (7-point neuroscore scale) and weight of animals [ 14 ]. Another study showed that intranasal administration of methylprednisolone to mice with experimental autoimmune encephalomyelitis (EAE) suppressed the neuroinflammatory response and reduced immune cell infiltration and demyelination, in a similarly way to intravenous administration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar results have been observed in a 60-min middle cerebral artery occlusion stroke model. IN DEX reduced strikingly the ischemic brain tissue damage, reduced blood-brain barrier permeability, decreased mortality and improved the Neurological deficit (7-point neuroscore scale) and weight of animals [ 14 ]. Another study showed that intranasal administration of methylprednisolone to mice with experimental autoimmune encephalomyelitis (EAE) suppressed the neuroinflammatory response and reduced immune cell infiltration and demyelination, in a similarly way to intravenous administration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their therapeutic value is enormous in a wide range of autoimmune/inflammatory diseases, and GCs have been widely used for treating autoimmune disorders, allergies, allograft rejection, neuroinflammation, and neoplastic diseases [ 10 ]. In this context, DEX, a potent anti-inflammatory synthetic GC, has been used to reduce inflammation in different neuroinflammatory conditions [ 14 , 17 , 37 ]. In the present study, we showed that treatment with L/DEX (0.05 mg/kg BW) and M/DEX (0.25 mg/kg BW) through the IN route in the murine pulmonary TB model significantly decreased neuroinflammation, improving behavioral status without aggravating lung disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations